ETUDE FAUNISTIQUE DE LA FORÊT D’ACHEMECHE PROVINCE D’EL HAJEB/ COMMUNE RURALE DE RAS JERRY /MAROC - EL Mzaiti, Ikram; Zine, Nasser-Eddine; Boukil, Ahmed; Qaini, Taoufiq (European Scientific Journal, ESJ, 2015)
This faunistic study of the site Ait Oukhlfen 1 of the forest of Achemeche is situated in the rural district Ras Jerry; joins the framework of integration of biodiversity during the process of sustainable territorial development. This study allows us to identify several heritage species (endemic, rare, and threatened) including 5 reptiles, 5 mammals and 7 birds. Obviously, referring to the Moroccan Strategic Studies, regulations includes the Law 22-07 on the establishment areas of strict confidentiality, national biodiversity study, and finally the red list of the International Union of Conservation of Nature (IUCN)